2014
DOI: 10.1093/infdis/jiu566
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNFSF8 Regulatory Variants With Excessive Inflammatory Responses but not Leprosy Per Se

Abstract: Twin and family studies indicate that host genetic factors influence susceptibility to leprosy and, possibly , leprosy type. Murine studies have suggested a role for the natural resistance-associated macrophage protein 1 (Nramp1) gene, which can influence cellular immune responses to intracellular pathogens. We evaluated a variation in the human homolog, NRAMP1, recently associated with tuberculosis susceptibility in West Africa. A total of 273 patients with leprosy and 201 controls from Mali were genotyped fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…For example, we have previously shown for variants of the TNFSF15/TNFSF8 genes that leprosy patients with the T1R endophenotype are largely the cause of association with the leprosy exophenotype [16, 17] . Consequently, the replication of the TNFSF15/TNFSF8 association in samples of leprosy patients with a low proportion of T1R is expected to display low power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have previously shown for variants of the TNFSF15/TNFSF8 genes that leprosy patients with the T1R endophenotype are largely the cause of association with the leprosy exophenotype [16, 17] . Consequently, the replication of the TNFSF15/TNFSF8 association in samples of leprosy patients with a low proportion of T1R is expected to display low power.…”
Section: Discussionmentioning
confidence: 99%
“…The replication sample was of Vietnamese ethnicity and encompassed 253 T1R-affected and 563 T1R-free leprosy patients. The validation sample comprised 471 T1R-affected subjects and 446 T1R-free leprosy patients as controls from the Central-west and South-east regions of Brazil as described previously [16, 37, 38]. In both replication and validation samples, cases and controls were matched for leprosy subtype.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increased TL1A expression in RA, genetic variants near TNFSF15 have not been found to contribute to RA risk. Interestingly, studies in Vietnamese [120], Indian, and West African [121] leprosy cohorts have been unable to replicate genetic association with the TNFSF15 locus, suggesting population-specific effects or disease heterogeneity among the cohorts included [122]. Interestingly, the TNFSF15 locus was also found to be associated with leprosy in a GWAS of Chinese individuals [118,119], adding to the list of IBDassociated loci that are shared with mycobacterial diseases.…”
Section: Tl1a In Human Diseasementioning
confidence: 99%
“…Along with evidence from mouse models of bacterial [25] and viral infection [33], this genetic association raises the possibility of TL1A having a positive role in protection from pathogens. Interestingly, studies in Vietnamese [120], Indian, and West African [121] leprosy cohorts have been unable to replicate genetic association with the TNFSF15 locus, suggesting population-specific effects or disease heterogeneity among the cohorts included [122].…”
Section: Tl1a In Human Diseasementioning
confidence: 99%
“…A prospective study of host responses to M. leprae antigen identified a gene-set signature that predisposed to T1R 12 . In addition, candidate gene approaches identified six protein coding genes in association with T1R [13][14][15][16][17][18][19] . More recently a genome-wide association study (GWAS) identified a long noncoding RNA in chromosome 10 as T1R risk factor in independent populations and also provided suggestive evidence for the PRKN (formerly PARK2) as T1R susceptibility gene 18 .…”
mentioning
confidence: 99%